Fisheries College, University of Agricultural Sciences, Mangalore-1 - Gupta, T R Chandrasekhara (Indian Journal of Fisheries, 2011)
An instance of intestinal abnormality in the ribbon fish, Trichiuruslepturus Linnaeus is described. The intestine was unusually short, opening ata much anteriorly shifted anal aperture which, in the normal condition, remainsclose to the urinogenital aperture.